You can't joke about that ebook Why everything is funny, nothing is sacred, and we're all in this together. - Timpf, Kat (2023)
What happens when we can't joke about some of the most important stuff in life? In a 2019 study, 40% of people reported censoring themselves out of fear that voicing their views would alienate them from the people they care about most. Those people should probably not read this book in public. In You Can't Joke About That, Kat Timpf shows why much of the way we talk about sensitive subjects is wrong. We've created all the wrong rules. We push ourselves into unnecessary conflicts when we should feel like we're all in this together. When someone says "you can't joke about that," what they really mean is "this is a subject that makes people sad or angry." Hilariously and movingly, Timpf argues that those subjects are actually the most important to joke about. She shows us we can find healing through humor regarding things you probably don't want to bring up in polite conversation, like traumatic break-ups, cancer, being broke, Dave Chappelle, rape jokes, aging, ostomy bags, religion, body image, dead moms, religion, the lab leak theory, transgender swimmers, gushing wounds, campus censorship, and bad Christmas presents. This book is Kat Timpf with her hair down, except since hers is mostly extensions, this book is Kat Timpf with her hair out. Read it because you want to get to know her better. Read it because it's the best book on free speech and comedy in a generation. Read it because you want to laugh out loud... even at the kind of stuff we're afraid to say out loud. Just read it, and you'll be glad you did.